You are on page 1of 23

Department of Electromechanical Engineering

Modern Control System

1 / 23
Chapter-2: Solutions of state space equations

1 Solution of Homogeneous State Equations


Laplace Transform Approach

2 Solution of Nonhomogeneous State Equations


Laplace Transform Approach

3 Computation of φ(t)
Inverse Laplace Transform
Similarity Transformation
Caley Hamilton Theorem

2 / 23
Solution of Homogeneous State Equations

Solution of Homogeneous State Equations


In this section, we shall obtain the general solution of the state
equation. We shall first consider the homogeneous case and then
the nonhomogeneous case.

Before we solve vector-matrix differential equations, let us review


the solution of the scalar differential equation
ẋ = ax
In solving this equation, we may assume a solution x(t) of the form
x(t) = b0 + b1 t + b2 t 2 + . . . + bk t k + . . .
By substituting this assumed solution into the above state equation,
we obtain
b1 +2b2 t+3b3 t 3 +. . . +kbk t k−1 +. . . = a(b0 +b1 t+b2 t 2 +. . . +bk t k +. . . )
3 / 23
Solution of Homogeneous State Equations

If the assumed solution is to be the true solution and equating the


coefficients of the equal powers of t, we obtain
b1 = ab0
ab1 a2 b0
b2 = =
2 2
ab2 a3 b0
b3 = =
3 2∗3
.
.
.
ak b0
bk =
k!
The value of b0 is determined by substituting t = 0 into the solution,
x(0) = b0
4 / 23
Solution of Homogeneous State Equations

Hence, the solution x(t) can be written as


a2 t 2 a3 t 3 ak t k
x(t) = (1 + at + + + ... + + + . . . .)x(0)
2! 3! k!

X (at)n
= e at x(0) = x(0)
n!
n=0
We shall now solve the vector-matrix differential equation
ẋ = Ax
Where x = n-vector
A = n*n-constant matrix
By analogy with the scalar case, we assume that the solution is in
the form of a vector power series in t, or
x(t) = b0 + b1 t + b2 t 2 + . . . + bk t k + . . .
By substituting this assumed solution into the differential state equa-
tion, we obtain
5 / 23
Solution of Homogeneous State Equations

b1 +2b2 t+3b3 t 3 +. . . +kbk t k−1 +. . . = A(b0 +b1 t+b2 t 2 +. . . +bk t k +. . . )


If the assumed solution is to be the true solution, and equating the
coefficients of like powers of t on both sides of the above equations,
we obtain
b1 = Ab0
Ab1 A2 b0
b2 = =
2 2
Ab2 A3 b0
b3 = =
3 2∗3
.
.
.
k
A b0
bk =
k! 6 / 23
Solution of Homogeneous State Equations

By substituting t = 0 into the solution equation, we obtain

x(0) = b0

Thus, the solution x(t) can be written as

A2 t 2 A3 t 3 Ak t k
x(t) = (I + At + + + ... + + + . . . .)x(0)
2! 3! k!
The expression in the parentheses on the right-hand side of this
last equation is an n ∗ n matrix. Because of its similarity to the
infinite power series for a scalar exponential, we call it the matrix
exponential and write

x(t) = e At x(0)

7 / 23
Solution of Homogeneous State Equations
Laplace Transform Approach

Laplace Transform Approach


Let us first consider the scalar case:

ẋ = ax

Taking the Laplace transform, we obtain

sX (s) − x(0) = aX (s)

and
x(0)
= (s − a)−1 x(0)
X (s) =
s −a
The inverse Laplace transform of this last equation gives the solution

x(t) = e at x(0)

8 / 23
Solution of Homogeneous State Equations
Laplace Transform Approach

The previous approach can be extended to the homogeneous state


equation:
ẋ = Ax
Taking the Laplace transform of both sides of the equation, we
obtain
sX(s) − x(0) = AX(s)
and
(sI − A)X(s) = x(0)
The inverse Laplace transform of X(s) gives the solution x(t).Thus,
x(t) = [(sI − A)−1 ]x(0)
Note that
1 A I A A2
(sI − A)−1 = [I − ]−1 = + 2 + 3 + . . .
s s s s s
1
= 1 + x + x 2 + x 3 + ...
1−x
9 / 23
Solution of Homogeneous State Equations
Laplace Transform Approach

Hence, the inverse Laplace transform of (sI − A)−1 gives

A2 t 2 A3 t 3
L (sI − A)−1 = I + At + + + . . . = e At
2! 3!
The inverse Laplace transform of a matrix is the matrix consisting
of the inverse Laplace transforms of all elements. Therefore, the
solution is obtained as

x(t) = e At x(0)

Therefore, the general solution is given by

x = φ(t)x(0)

where φ(t) = e At is State Transition Matrix

10 / 23
Solution of Homogeneous State Equations
Laplace Transform Approach

Example:Obtain the state-transition matrix φ(t) of the following


system:     
ẋ1 0 1 x1
=
ẋ2 −2 −3 x2
and obtain also the inverse of the state-transition matrix, φ−1 (t)

11 / 23
Solution of Nonhomogeneous State Equations

Solution of Nonhomogeneous State Equations


We shall begin by considering the scalar case

ẋ = ax + bu

Multiplying both sides of this equation by e −at , we obtain


d −at
e −at [ẋ − ax(t)] = [e x(t)] = e −at bu(t)
dt
Integrating this equation between 0 and t gives
Z t
−at
e x(t) − x(0) = e −aτ bu(τ )dτ
0
or Z t
at
x(t) = e x(0) + e a(t−τ ) bu(τ )dτ
0
12 / 23
Solution of Nonhomogeneous State Equations

The first term on the right-hand side is the response to the initial
condition and the second term is the response to the input u(t).

Let us consider the nonhomogeneous state equation described by


ẋ = Ax + Bu
Where x=n*1 vector
u = m*1-vector
A = n*n constant matrix
B = n*m constant matrix

pre multiplying both sides of this equation by e -At , we obtain


d
e -At [ẋ − Ax(t)] = [e −At x(t)] = e -At Bu(t)
dt
Integrating this equation between 0 and t gives
Z t
-At
e x(t) − x(0) = e −Aτ Bu(τ )dτ
0 13 / 23
Solution of Nonhomogeneous State Equations

or Z t
x(t) = e At x(0) + e A(t−τ ) Bu(τ )dτ
0
The above equation can also be written as
Z t
x(t) = φ(t)x(0) + φ(t − τ )Bu(t)dτ
0
The above equation is the State Transition Equation

The solution x(t) is clearly the sum of a term consisting of the


transition of the initial state and a term arising from the input vector.

Thus far we have assumed the initial time to be zero. If, however,
the initial time is given by t0 instead of 0, then the solution must
be modified to
Z t
A(t−t0 )
x(t) = e x(t0 ) + e A(t−τ ) Bu(τ )dτ
t0
14 / 23
Solution of Nonhomogeneous State Equations
Laplace Transform Approach

Laplace Transform Approach


The solution of the nonhomogeneous state equation
ẋ = Ax + Bu
can also be obtained by the laplace transform approach. The laplace
transform equation yields
(sI − A)X(s) = x(0) + BU(s)
The inverse laplace transform of the above equation can be obtained
by convolution integral as follows:
Z t
At
x(t) = e x(0) + e A(t−τ ) Bu(τ )dτ
0
Therefore, the output response y (t) is the sum of zero-input re-
sponse and zero-state response
Z t
At
y (t) = C[e x(0) + e A(t−τ ) Bu(τ )dτ ] + Du(t)
0 15 / 23
Solution of Nonhomogeneous State Equations
Laplace Transform Approach

Example: Obtain the time response of the following system:


      
ẋ1 0 1 x1 0
= + u
ẋ2 −2 −3 x2 1

If the initial state is zero, or x(0) = 0, and u(t) is the unit-step


function occurring at t = 0

16 / 23
Computation of φ(t)
Inverse Laplace Transform

Inverse Laplace Transform

For the system ẋ(t) = Ax(t) + Bu(t), the state transition matrix
e At can be computed as,

e At = L−1 [(sI − A)−1 ]


 
1 1
Example: For the system ẋ(t) = Ax(t)+Bu(t), where A = .
−1 1
compute e At using Inverse Laplace transform method.

17 / 23
Computation of φ(t)
Similarity Transformation

Similarity Transformation
If Ā is the diagonal representation of the matrix A, then Ā =
T −1 AT . When a matrix is in diagonal form, computation of state
transition matrix is straight forward:
 λ1 t 
e 0 ... 0
 0
 e λ2 t ... 0  
Āt
 . . ... . 
e =  .

 . ... .  
 . . ... . 
0 0 ... e λn t
Given e Āt , we can show that
e At = Te Āt T −1
A2 t 2 A3 t 3 Ak t k
T −1 e At T = T −1 (I + At + + + ... + + + . . . .)T
2! 3! k!
18 / 23
Computation of φ(t)
Similarity Transformation

If matrix A involves multiple eigenvalues, then diagonalization is


impossible. For example, if the 4x4 matrix A, where
 
0 1 0 0
 0 0 1 0 
A=  0

0 0 1 
−a4 −a3 −a2 −a1
has the eigenvalues λ1 , λ1 , λ1 , λ4 then the transformation x = Sz,
where  
1 0 0 1
λ1 1 0 λ4 
S= λ 2λ1 1 λ2 
2

1 4
λ31 3λ21 3λ1 λ34
will yield  
λ1 1 0 0
 0 λ1 1 0 
J = S−1 AS =   0 0 λ1 0 

0 0 0 λ4 19 / 23
Computation of φ(t)
Similarity Transformation

Therefore, the state transition matrix for a Jordan canonical form is

te λ1 t 12 t 2 e λ1 t
 λ1 t 
e 0
 0 e λ1 t te λ1 t 0 
e At = Se Jt S−1 = S 
 0 λ t
 S−1
0 e 1 0 
0 0 0 e λ4 t

Example: Consider the following matrix A


 
0 1 0
A = 0 0 1
1 −3 3

Compute the state transition matrix e At using similarity transforma-


tion

20 / 23
Computation of φ(t)
Caley Hamilton Theorem

Caley Hamilton Theorem


Every square matrix A satisfies its own characteristic equation. If
the characteristic equation is

∆(λ) = |λI − A| = λn + a1 λn−1 + a2 λn−2 + ... + an−1 λ + an

then,

∆(A) = An + a1 An−1 + a2 An−2 + ... + an−1 A + an

Application: Evaluation of any function f (λ) and f (A)

f (λ) = a0 + a1 λ + a2 λ2 + ... + an λn + ... order ∞

f (λ) g (λ)
= q(λ) +
∆(λ) ∆(λ)
21 / 23
Computation of φ(t)
Caley Hamilton Theorem

Therefore,
f (λ) = q(λ)∆(λ) + g (λ)
= g (λ)
= b0 + b1 λ + b2 λ2 + ... + bn−1 λn−1 order n−1
If A has distinct eigenvalues λ1 , ..., λn , then,
f (λi ) = g (λi ) i = 1, ..., n
The solution will give rise to b0 , b1 , ..., bn−1 , then
f (A) = b0 I + b1 A + ... + bn−1 An−1
If there are multiple roots (multiplicity = 2), then
f (λi ) = g (λi )
d d
f (λi ) = g (λi )
dλi dλi
22 / 23
Computation of φ(t)
Caley Hamilton Theorem

 
0 0 −2
Example 1: If A = 0 1 0  then compute the state transition
1 0 3
matrix using Caley Hamilton Theorem.

sol: b0= e 2t − 2te t , b1 = 3te t + 2e t 2t 2t t


 − 2e , b1 = e − e − te
t
t
2e − e 2t t
0 2e − 2e 2t

e At =  0 et 0 
2t
e −e t 0 2e − e2t t

Exercise:
  For the system ẋ(t) = Ax(t) + Bu(t), where A =
1 1
. compute e At using similarity transformation and Caley
−1 1
Hamilton theorem.

23 / 23

You might also like